2013
DOI: 10.1016/j.jagp.2013.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Phobic Anxiety and Cognitive Performance Over 4 Years Among Community-Dwelling Older Women in the Nurses' Health Study

Abstract: Objective To examine the relation of phobic anxiety to late-life cognitive trajectory. Design Prospective cohort. Setting Nurses’ Health Study – U.S. registered nurses. Participants 16,351 women among whom phobic anxiety symptoms were assessed in 1988 (mean age=63 years). Measurements Beginning a decade after phobic anxiety ascertainment (mean age=74 years), three assessments of general cognition, word and paragraph immediate and delayed recall, category fluency, and attention/working memory were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…In additional analyses, logistic regression models were used to calculate odds ratios for the highest CCI score (≥6) vs. lower scores (0-5) across quartiles of the three different FlOPs. Although prior work 32,34 indicates that a score of ≥6 on the CCI may indicate a critical threshold of anxiety symptoms, there may be other important contrasts involving sub-threshold levels of anxiety, which have been addressed in prior NHS investigations 4,45 . Thus, we also utilized polytomous logistic regression models to investigate the relations of continuous log transformed FlOPs to finer contrasts of phobic anxiety rather than just the dichotomized approach; in these models, persons scoring 0/1 on the CCI served as the reference group for comparisons with those in all higher categories of phobic anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…In additional analyses, logistic regression models were used to calculate odds ratios for the highest CCI score (≥6) vs. lower scores (0-5) across quartiles of the three different FlOPs. Although prior work 32,34 indicates that a score of ≥6 on the CCI may indicate a critical threshold of anxiety symptoms, there may be other important contrasts involving sub-threshold levels of anxiety, which have been addressed in prior NHS investigations 4,45 . Thus, we also utilized polytomous logistic regression models to investigate the relations of continuous log transformed FlOPs to finer contrasts of phobic anxiety rather than just the dichotomized approach; in these models, persons scoring 0/1 on the CCI served as the reference group for comparisons with those in all higher categories of phobic anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…The CCI score was calculated and categorized into 5 groups as follows: <2 (the reference group); 2-<3; 3-<4; 4-<6; and 6 or above (the highest phobic anxiety symptoms group) (26). We used Cox proportional-hazards models to estimate the hazard ratios (HRs) and 95% confidence intervals (CI) of developing T2D across the 5 categories of the CCI; the comparison group was participants with CCI <2.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers begin to postulate that anxiety may be an early sign of neurodegenerative disorders. However, findings from recent prospective studies on anxiety and cognitive decline are still inconclusive due to the heterogeneity in anxiety and cognitive measurements used in the literatures . Of those prospective studies, only 4 reported positive results in relation to cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Pietrzak et al (2012) found evidences for decline in visual learning and memory in anxious older adults, while others reported decline in executive functioning in participants with generalized anxiety disorders . The null findings in others may be explained by different sampling frame and the use of a less specific test for cognitive functioning . It is still unclear as to whether poor cognitive performance in older adults is a result of suffering from anxiety disorders, or merely reflecting other concomitant condition that impairs cognition in the ageing brain.…”
Section: Introductionmentioning
confidence: 99%